THE RELATIONSHIP OF ORGANIZATIONAL FACTORS AND COMPLIANCE LEVEL IN THE APPLICATION OF STANDARD PRECAUTIONS - Sahri, Moch.; Zuhro, Ramdhoni; Hutapea, Octavianus; Dwimarisiana, Warsiki (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Infection prevention around health care facilities is one of the efforts to minimize infection in patients, officers, visitors, and communities. One of the efforts to prevent infection is to apply standard precautions. Purpose: To determine the effect of organizational factors on the level of compliance of health workers in implementing standard precautions. Method: There were 83 respondents. The sampling technique uses simple random sampling. The dependent variable is the level of compliance with the application of standard precautions. The independent variables are policies, procedures, facilities, training, monitoring, and safety climate. Data analysis using correlation test and regression test to determine the effect between variables. Result: There was a relationship between facilities and the level of compliance (p = 0.030), there was a relationship between training and compliance (p = 0.027), there was a relationship between the safety climate and the level of compliance (p = 0,009). The influence test shows that the climate safety factor (p = 0.007) and facilities (p = 0.020) have a significant effect on the level of compliance. Conclusion: There is a relationship between facilities training and safety climate with the level of compliance of officers in the application of standard precautions in hospitals. The factor that most influences the level of compliance with the application of standard precautions is the safety climate.